Bilateral investment treaty interpretation: An internationalist spirit tempered by context: Government of the Laos People’s Democratic Republic v Sanum Investments Ltd - MOHAN, Mahdev (Institutional Knowledge at Singapore Management University, 2015)
This commentary discusses the first Singapore court decision to have interpreted a BIT to which Singapore is not a party. The case concerns a dispute between the Laos People’s Democratic Republic (“Laos”) and Sanum Investments Limited (“Sanum”), a company in corporated in Macau. The Court had to determine whether a bilateral investment treaty (“BIT”) between Laos and the People’s Republic of China (the “PRC-Laos BIT”) extended to Macau, which was handed over to China after the conclusion of the treaty. The Court concluded that neither the PRC nor Laos had intended for the treaty to apply to Macau. Further, the Court held that Sanum’s expropriation claims against the Laotian government fell outside the scope of the treaty. The decision turned on the relevant canons of treaty interpretation in light of the context within which the PRC-Laos BIT was drafted and subsequent agreements.